Dengue a Worldwide Threat: Need to be Ceased with Systematic Scientific Measures to Stop its Fast Desolation Throughout the World - Ibrahim, Muhammad (International Journal of Pathology, 2023)
Dengue virus belongs to family Flaviviridae and genus Flavivirus, transmitted primarily in a cycle through human beings and mosquito vector. The rate of incidence of dengue fever epidemics has reached to the highest, since past few years. Over a geologically expanding area, the level of hyperendemic transmission has been established. The person with sequential dengue infection is also victim of dengue hemorrhagic fever (DHF) which is the most sever disease. The rate of incidence of DHF and the possibility of sequential infections, has increased intensely, first of all in Asian countries and currently in America. The wide spreading of mosquito Aedesaegypti is even more alarming. As a consequence of insufficiency of antiviral drugs and potential vaccine, a large number of individuals are infected with severe dengue virus every year which causes huge death cases.Conclusion: Presently, to prevent epidemics, controlling the dengue mosquito is the only available method. New investigation fordiscovery of potential vaccine, evaluation of vector control tools and approaches are desirable